Common pediatric medical procedures. Intravenous access - Baum, Rebecca; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2018)
A complete review and demonstration of intravenous access techniques, including equipment setup, positioning, pain management, and methods for calming and reassuring the child.
Presenter: Rebecca Baum.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 15, 2020)
Keywords: Intravenous therapy; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films